Expression level of interferon-stimulated genes PKR, OAS1, MX1, and ISG15 in peripheral blood mononuclear cells of COVID-19 patients: A retrospective study - Elham Jafari Maskouni; Samaneh Abbasi; Elham Mousavi; Zahra Najafimemar; Ali Mohammad Arabzadeh; Mehrdad Farrokhnia; Saeedeh Ebrahimi (Journal of Acute Disease, 2024)
Objective: To explore expression level of interferon-stimulated genes PKR, OASI, MX1, and ISG15 in peripheral blood mononuclear cells of COVID-19 patients. Methods: In this study, changes in the expression of four interferon-stimulated genes (ISGs), including PKR, OASI, MX1, and ISG15, in peripheral blood mononuclear cells of 45 COVID-19 patients with different severities were evaluated by real-time PCR method. Results: OASI, MX1, PKR, and ISG15 were differently expressed in COVID-19 patients with different severity. The results showed that the expression of OASI, MX1, PKR, and ISG15 genes was significantly (P=0.001) lower in severe patients. Conclusions: Weak and defective IFN response and subsequent disruption of ISGs may be associated with COVID-19 severity.